From the morphological to the transcriptomic characterization of a compromised three‐dimensional in vitro model mimicking atopic dermatitis. (1st October 2015) - Rouaud‐Tinguely, P.; Boudier, D.; Marchand, L.; Barruche, V.; Bordes, S.; Coppin, H.; Roth, M.P.; Closs, B.
Summary: Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease in which skin barrier function is disrupted. In this AD environment, proinflammatory cytokines are upregulated, promoting a vicious circle of inflammation. Although several three‐dimensional in vitro models mimicking AD have been published, no study has presented a fully characterized and controlled model of AD‐related inflammation. Objectives: To develop and characterize, from the morphological to the molecular level, a compromised reconstructed epidermis (RE) mimicking AD‐related inflammation in vitro . Methods: Normal human keratinocytes were used to generate RE, treated or not with an inflammatory cocktail (polyinosinic–polycytidylic acid, tumour necrosis factor‐α, interleukin‐4 and interleukin‐13). Results: The inflammatory cocktail induces some modifications observed in patients with AD: (i) it leads to spongiosis; (ii) it alters early and terminal differentiation proteins; (iii) it increases thymic stromal lymphopoietin and interleukin‐8 secretion by keratinocytes and (iv) it results in a specific gene expression pattern. Conclusions: The inflammatory context contributes to the morphological, functional and transcriptomic changes observed in AD skin. As a result, this compromised RE model shares some characteristics with those found in AD skin and thus can be used as a relevant tool for screening formulations and drugs for the treatment of AD.